2008
DOI: 10.1016/j.jacc.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Lymphatic Vascular Disease

Abstract: The lymphatic vasculature is comprised of a network of vessels that is essential both to fluid homeostasis and to the mediation of regional immune responses. In health, the lymphatic vasculature possesses the requisite transport capacity to accommodate the fluid load placed upon it. The most readily recognizable attribute of lymphatic vascular incompetence is the presence of the characteristic swelling of tissues, called lymphedema, which arises as a consequence of insufficient lymph transport. The diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
110
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 71 publications
0
110
0
Order By: Relevance
“…Increased lymphatic flow rate might be associated with interstitial edema caused by LAD ligation. Moreover, lymphatic flow impairment caused by lymphatic disruption or flow resistance may occur in some diseases such as AMI and mediastinal lymphadenopathy, in which functional lymphangiogenesis (lymphatic vessel regeneration) will improve cardiac lymph flow (Rockson, 2008). In our study, potent lymphangiogenetic factors including VEGF-C and D, Prox-1, and Lyve-1 were significantly expressed in the peri-infarction areas after AMI.…”
Section: Discussionmentioning
confidence: 51%
“…Increased lymphatic flow rate might be associated with interstitial edema caused by LAD ligation. Moreover, lymphatic flow impairment caused by lymphatic disruption or flow resistance may occur in some diseases such as AMI and mediastinal lymphadenopathy, in which functional lymphangiogenesis (lymphatic vessel regeneration) will improve cardiac lymph flow (Rockson, 2008). In our study, potent lymphangiogenetic factors including VEGF-C and D, Prox-1, and Lyve-1 were significantly expressed in the peri-infarction areas after AMI.…”
Section: Discussionmentioning
confidence: 51%
“…Hypoplasia, disruption or dysfunction of the lymphatic vessels, impair the ability of the lymphatic vasculature to collect and transport fluids and lead to lymphedema. 1,2 The mammalian lymphatic system has been shown to originate from embryonic veins. Lymphatic vessel development starts at embryonic days (E) 9.5 to 10.5 in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Hammil et al 4 showed that the use of the mTOR (mammalian target of sirolimus) inhibitor sirolimus, with its tolerable side effects, significantly improved clinical conditions of the patients. In this study, it is also showed that sirolimus is effective and reliable in the treatment of life-threatening vascular anomalies, and it should be used as an important treatment approach 5 .…”
mentioning
confidence: 75%
“…Complete decongestive physiotherapy (CDT), which is the most common and the most effective treatment method in lymphedema, is a multicomponent approach aiming to decrease the extremity volume, maintain the skin health, and support the structures 5 . Manual therapy is used in physiotherapy for pain and joint limitations 8 .…”
mentioning
confidence: 99%